Environmental conceptions and the ideological commitments that guide the management of the environmental organizations - Silva, José Kennedy Lopes; Siena, Osmar (Revista de Administração da UFSM, 2020)
Environmental organizations actively take part in the proposition of strategies, studies and environmental practices that aim at reducing the environmental degradation of the planet. These organizations have conceptions and commitments that guide their actions. The objective of the research that led to this article was to understand the environmental conceptions and the ideological commitments that guide the actions and the management of the environmental organizations. The research focused on three environmental organizations, two located in the state of Mato Grosso and one in the state of Rondônia, all of them belonging to the Brazilian Legal Amazon region. A qualitative research with multiple case study was carried out. Participant observation, semi-structured interviews and documentary analysis were used as strategies. Several environmental conceptions that influence the performance and management of organizations were identified, with a greater presence of the socio-environmentalist and of the environmental justice conceptions. However, the latter is not discussed strategically. Regarding the ideological commitments, the eco-socialist vision is the one that seems to have more influence over organizations.